2016
DOI: 10.1111/inm.12264
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of wake and light therapy in patients with depression: A qualitative study

Abstract: Wake therapy can reduce depressive symptoms within days, and response rates are high. To sustain the effect, it is often combined with light therapy. Few studies have focussed on factors related to patients' adherence to the regime, and none has used qualitative methods to examine their experience of these combined interventions. Therefore, the aim of the present study was to illuminate patients' experiences with wake and light therapy and factors related to adherence. Thirteen inpatients with depression were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Performing a task successfully may increase self‐efficacy , and this might explain why self‐efficacy increased significantly more in the wake therapy group. This agrees with our previous findings (Kragh et al 2016) in the qualitative study of depressive patients’ experience of combined wake and light therapy, where it was described as a personal victory to have completed the intervention . The combination of wake therapy, light therapy and sleep time stabilization seems to have a positive impact on patients’ sleep.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Performing a task successfully may increase self‐efficacy , and this might explain why self‐efficacy increased significantly more in the wake therapy group. This agrees with our previous findings (Kragh et al 2016) in the qualitative study of depressive patients’ experience of combined wake and light therapy, where it was described as a personal victory to have completed the intervention . The combination of wake therapy, light therapy and sleep time stabilization seems to have a positive impact on patients’ sleep.…”
Section: Discussionsupporting
confidence: 91%
“…Some answered that they would not choose the treatment if they became depressed again. However, they would consider chronotherapeutic intervention if they again experienced severe sleep problems .…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the included controlled trials and the results for each outcome are presented below separately for the comparison of i) SD as add‐on compared with standard treatment ii) for the comparison of SD versus other treatment. Apart from the studies above, seven case series 30–36 were included for the evaluation of rate of complications following SD and one qualitative study 37 contributed information regarding patients’ experience during treatment. Total rather than partial SD was used in all the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Only one qualitative study was found to focus on patients’ experiences of SD when taking part in an RCT 37 . The quality of the study was evaluated as moderate because of lack of information on ethical rational (ie power imbalances during interviewing) and theoretical foundation (ie insufficient presentation of manifest analysis).…”
Section: Resultsmentioning
confidence: 99%
“…This kind of thinking and verbal behavior increases motivation for changes in behavior. Although the behavior that delivers light treatment may seem simple and straightforward to the clinician, one should not assume that it looks this way to a patient, especially a depressed patient who is likely to be fatigued, pessimistic, and low in self-efficacy [16]. This MI process consists of the clinician modeling this attitude in his or her own talk, and explicitly acknowledging change talk exhibited by the patient, stating that it is positive and will contribute to behavior change, and, thereby, symptom reduction and improved functioning.…”
Section: Motivation Enhancementmentioning
confidence: 99%